2022
DOI: 10.4285/kjt.22.0001
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory diagnostic testing for cytomegalovirus infection in solid organ transplant patients

Abstract: Human cytomegalovirus (CMV) infection, which is one of the most common complications in transplant recipients, increases the risk of graft loss and rejection. Laboratory strategies for diagnosing CMV infection rely on the measurement of viral DNAemia and CMV-specific cell-mediated immunity (CMV-CMI). The CMV quantitative nucleic acid amplification test (QNAT) enabled the spread of preemptive therapy and prompted recommendations for surveillance, diagnosis, and monitoring. Despite the implementation of the Worl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 90 publications
(156 reference statements)
0
9
0
Order By: Relevance
“…Pretransplant CMV-CMI has been suggested as a risk for posttransplant CMV replication. [2][3][4]17,[21][22][23][24] We selected 44 HLA alleles to analyze the CMV-ELI-SPOT results based on HLA allele frequencies. The frequencies of these 44 HLA alleles in our study were comparable to those found in previous reports (Table S2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pretransplant CMV-CMI has been suggested as a risk for posttransplant CMV replication. [2][3][4]17,[21][22][23][24] We selected 44 HLA alleles to analyze the CMV-ELI-SPOT results based on HLA allele frequencies. The frequencies of these 44 HLA alleles in our study were comparable to those found in previous reports (Table S2).…”
Section: Discussionmentioning
confidence: 99%
“…This requires special attention in identifying risk factors associated with CMV reactivation. Pretransplant CMV‐CMI has been suggested as a risk for posttransplant CMV replication 2–4,17,21–24 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CMV-specific IgG antibodies are screened for in both donors and recipients, as serostatus is the most important predictor of CMV risk following transplantation [14,15]. Solid organ transplantation, particularly from seropositive donors (D+) to seronegative patients (R-), confers the single greatest risk for both transmission and developing clinically significant CMV infection [16][17][18][19]. In seronegative recipients, up to 58% of transplant recipients from seropositive donors (D+/R-) can develop clinically significant CMV infections if prophylactic antivirals are not taken, while this risk can be as low as 2.4% if serostatus is D-/R- [5,20].…”
Section: Serologic Risk Factorsmentioning
confidence: 99%
“…Cell and tissue culture, although highly specific, have very limited practical utility in the prevention, diagnosis, and treatment of CMV in SOT patients due to long turnaround time for testing. Despite the growing availability of CMV-specific cell-mediated immune assays such as interferon gamma release assay (QuantiFERON, ELISpot) for posttransplant risk stratification, their role in the prevention and treatment of CMV infection has yet to be established [12,18,62].…”
Section: Diagnosismentioning
confidence: 99%